Standardisation and the Wealth of Place Names - Jaillard, Pierre; Jordan, Peter; Rieger, Marie Antoinette; Mamvura, Zvinashe; Khanyetsi, Palesa Mabohlokoa Khotso; Jeney, János; de Menezes, Paulo Márcio Leal; Fernandes, Manoel do Couto; Santos, Kairo da Silva; Janeiro, Júlia Vellasquez; Dantas, Victor Gabriel da Silva; Ferreira, Gabriela Calafate; et al. (UJ Press, 2025)
Standardisation and the Wealth of Place Names – Aspects of a Delicate Relationship is a selection of double-blind peer-reviewed papers from the 6th International Symposium on Place Names that took place virtually 29 September – 1 October 2021. The symposium explored the issues of multiple place names vis-à-vis processes of standardisation. These studies collectively show that there is not a simplistic dichotomy between standardisation and the protection of cultural heritage. Some papers grapple with the implications and execution of standardisation processes, while others explore the emergence of alternative or unofficial names in response to top-down initiatives. The matter of signed place names also receives some attention. A number of papers excavate the layers of multiple place names, thereby contributing to our ‘wealth’ of toponymic knowledge. These proceedings are the product of collaboration between Southern African and international researchers. As such, it is a valuable resource to local as well as international scholars who are interested in the interdisciplinary field of toponymy.